An observation on three local bilingual musicals in Malaysia - Toon, Elaine; Loo, Fung Chiat (UPM Press, 2015)
Malaysia is known for the diversity within its cultures and ethnic groups.According to the official Malaysian government portal site, the official language here is Bahasa Melayu, or the Malay language, and most Malaysians can verbalize more than one language or dialect. Grosjean (1982) in the introduction to his journal ‘Life with Two Languages’ expressed that the majority of Malaysia’s population is bilingual or multilingual. Bloomfield’s (1933:55) definition of bilingualism ranges from ‘a minimal proficiency in two languages’ to ‘and advanced level of proficiency which allows the speaker to function and appear as a native-like speaker of two languages’. This is the reason why the utilization of bilingualism or multilingualism is not an alien phenomenon in this country.